The Influence of Profitability, Leverage and Sales Growth on Tax Avoidance in Food and Beverage Sector Companies Listed on the Indonesian Stock Exchange - Samos, Yudi Febrianto; Rialdy, Novien; Sanjaya, Surya (International Journal of Multidisciplinary Approach Research and Science, 2024)
The purpose of this study are: (1) find out and analyze the effect of profitability on tax avoidance, (2) find out and analyze the effect of leverage on tax avoidance, (3) find out and analyze the effect of sales growth on tax avoidance, and (4) find out and analyze profitability, leverage and sales growth which together have an effect on tax avoidance. The population in this study are all food and beverage companies listed on the Indonesia Stock Exchange as many as 30 companies and the research sample as many as 11 companies with 3 years of observation. Data collection techniques in this study using documentation techniques. The data analysis technique in this study uses the Classical Assumption Test, Multiple Linear Regression, t-test and F-test, and the Coefficient of Determination. Data management in this study uses the SPSS V22.0 Software program. Based on the results of the study, it shows that profitability has a positive and significant effect on tax avoidance, leverage has a positive and significant effect on tax avoidance, sales growth has a positive and significant effect on tax avoidance, and profitability, leverage and sales growth has an effect on tax avoidance.